The Influence of Word of Mouth, Business Location, and Product Quality on Customer Satisfaction: An Islamic Business Management Perspective (A Study on Mie Gacoan Consumers at the Antasari Branch, Bandar Lampung) - Wahyuni, Shelly; A. Zuliansyah; Yulistia Devi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to investigate the influence of word of mouth, business location, and product quality on customer satisfaction from the perspective of Islamic business management. The research was conducted on consumers of Mie Gacoan at the Antasari branch in Bandar Lampung, employing a quantitative approach with data collected through questionnaires. The findings indicate that all three independent variables significantly affect customer satisfaction, both individually and collectively, with product quality emerging as the most dominant factor. Within the framework of Islamic business ethics, customer satisfaction is closely associated with the implementation of core values such as honesty (shidq) in communication, trustworthiness (amanah) in service delivery, and excellence (ihsan) in maintaining product quality. These results highlight the importance of integrating Islamic ethical principles into modern business practices to cultivate sustainable customer relationships and enhance trust in an increasingly competitive marketplace.